Agenda Setting Theory Pencalonan Walikota Jambi di Media Seru Jambi.com - Sobirin; Muhaimin; M. Junaidi; Dian Mursyidah (MAUIZOH: Jurnal Ilmu Dakwah dan Komunikasi, 2019)
This research is motivated by the reality of media coverage in constructing political figures for mayoral candidates who campaign through these media. Through the media agenda setting theory, the author examines the SeruJambi.com media in reporting Syarif Fasha as one of the candidates for the Jambi Mayor's candidate in 2018. The analysis goes through three things, namely: message framing, use of words and objectivity. The research method used is interpretive qualitative by emphasizing written sources in the form of documenting the contents of Syarif Fasha's news on the online media SeruJambi.com. The results of the study found that there was an imbalance in Seru Jambi.com in constructing the news of Syarif Fasha as one of the candidates for the Mayor of Jambi 2018. There is a message framing strategy in reporting the daily life of the candidate. The use of words with a simplification strategy from scientific language into everyday language, repetition of words as a pointer to the core idea of ​​the news, synonyms (similar words) by writing different words to prevent boredom. Similarity of topics to clarify a previous sentence, as a framing strategy to highlight the main idea of ​​the news